Impact of women's health initiative study on attitude and acceptance of hormone replacement therapy in Thai women attending menopause clinics - Sukanya Chaikittisilpa (2018)
Objective: To assess the attitude and acceptance of Thai women attending menopause clinics on hormone replacement therapy (HRT) after the Women's Health Initiative (WHI) publication. Material and Method: A standardized questionnaire was used to assess attitude and acceptance of HRT in 1,206 women who visited menopause clinics in six hospitals between September 2005 and February 2006. Results: Of the total respondents, 92% were in the age of 40-70 years, 75% were in their peri- and post menopause, 25% were current users and the average duration of hormone use was 5.6 ± 5.3 years. The women's perception of hormone benefits on osteoporosis prevention, skin improvement, and hot flashes treatment were 39.1%, 31.7%, and 28.9%, respectively. The most common concern of hormone use was malignancy. Hormone side effects were found to be the most common reason for switching hormone regimen. Of all the past users, 85% stopped HRT because they changed to another treatment regimen. Only 3.7% had been aware of the WHI, of which 43.5% were influenced by its results. The most common source of HRT information was from doctors. For the ever users, 72.3% had some knowledge about HRT. Conclusion: The present survey revealed that very few women had been aware of the WHI study. Nevertheless, the prevalence of HRT current users was lower compared to a prior survey before the WHI publication. Doctors appeared to be the important source of HRT information, which may indirectly have an influence over women's attitude and acceptance on HRT.